1964
DOI: 10.1002/macp.1964.020800118
|View full text |Cite
|
Sign up to set email alerts
|

Bisulfite‐initiated vinyl polymerization in aqueous media

Abstract: Bisulfite initiates aqueous polymerization of certain vinyl monomers such as methyl methacrylate, ethyl methacrylate, methacrylic acid and styrene but it fails in case of acrylonitrile, vinyl acetate, methylacrylate, and acrylic acid under identical conditions. The mechanism of initiation has been discussed. Catalyst exponent of this initiator with respect to methyl methacrylate is near about 0.5. Quantitative determination of endgroup by dye techniques of the polymers obtained show that about 2 sulfonate (‐SO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

1980
1980
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(19 citation statements)
references
References 10 publications
1
18
0
Order By: Relevance
“…They also proposed that both radicals do not recombine just after formed because of steric hindrance imposed by the methyl group attached to vinyl group. But in our case, neither of both monomers have a methyl group that could avoid recombination and, therefore, this lack should be counteracted by resonance stabilization of Figure 9 Initiation mechanism proposed by Mukherjee et al 21 applied to both monomers. Figure 10 Resonance stabilization of both radicals allowing initiation reaction.…”
Section: Sodium Disulfitementioning
confidence: 86%
See 1 more Smart Citation
“…They also proposed that both radicals do not recombine just after formed because of steric hindrance imposed by the methyl group attached to vinyl group. But in our case, neither of both monomers have a methyl group that could avoid recombination and, therefore, this lack should be counteracted by resonance stabilization of Figure 9 Initiation mechanism proposed by Mukherjee et al 21 applied to both monomers. Figure 10 Resonance stabilization of both radicals allowing initiation reaction.…”
Section: Sodium Disulfitementioning
confidence: 86%
“…Initiation by sodium bisulfite might be explained by a mechanism based on that proposed by Mukherjee et al 21 for monomers containing a methyl group attached to vinyl group. These authors proposed that bisulfite ion resulting from sodium disulfite dissociation in water attacks the vinyl group producing radicals in both species (see Fig.…”
Section: Sodium Disulfitementioning
confidence: 98%
“…Kim also noted the fall in the rate of polymerization at higher bisulfite although Mukherjee et al 4 did not observe such effects at 35OC when the concentration of NaHS03 was as high as 0.20 (m/l). Statistical treatment of the average rate data indicates that the average rate of polymerization is approximately inversely proportional to the 0.62 f 0.06 power of the metabisulfite concentrations.…”
Section: VIIImentioning
confidence: 92%
“…Konar and Palit2 reported that potassium or sodium bisulfite (HSO,) could initiate the aqueous polymerization of MMA at a pH of about 4-5 (due to the bisulfite alone) in the presence of nitrogen. They suggested that trace of air in the media might have generated the initiating free radicals by the known redox reaction3 H-SO, + 0 2 -+ SO, + HOa Mukherjee et al 4 later on reported that NaHS03 alone could initiate the aqueous and emulsion polymerizations of MMA, EMA, styrene, etc., but failed to initiate the polymerizations of AN, MA, acrylic acid, and vinyl acetate in the presence of nitrogen. They postulated an overall reaction for the initiating radical: Kim et al [5][6][7][8] reported recently that NaHS03 could initiate the aqueous polymerization of MMA and acrylamide easily, but the emulsion polymerizations of MA and AN could take place only in the presence of a cationic detergent micelles and in the presence of oxygen only.…”
Section: Introductionmentioning
confidence: 98%
“…In that work, we proved that DS could initiate AM/ADQUAT copolymerization itself, contrary to what was expected. Mukherjee et al 3 determined that sodium bisulfite (produced by the dissociation of DS in water) was able to produce radicals by a reaction with vinyl monomers having a methyl group on the double-bond carbon, avoiding radical recombination. In fact, no monomer used in that work had this methyl group contributing to steric hindrance, but the radical that formed was stabilized by resonance through the carbonyl group next to the double bond.…”
Section: Introductionmentioning
confidence: 99%